Effect of the Nematode-Trapping Fungus Dactylaria Brochopaga and the Nematode Egg Parasitic Fungus Verticilium Chlamydosporium in Controlling Citrus Nematode Infesting Mandarin, And Interrelationship with the Co Inhabitant Fungi - E.M.A, NOWEER; ., . (International Journal of Engineering and Technology, 2018)
In a field experiment, the nematode-trapping fungus Dactylaria brochopaga and the nematode egg parasitic fungus Verticilium chlamydosporium , was evaluated against the citrus nematode, Tylenchulus semipenetrans infesting Mandarin, Citrus reticulata, , the mixed compound was applied in October 2016 at the rate Â½ kg/tree, and root and soil samples were collected monthly until the next October, 2017. Successive treatment of the same mixed compound was added in the end of April 2017. For the comparison, Vydate 24% L. was applied as well as non treated check trees were left. Data revealed that the mixed compound treatment greatly affected the citrus nematode numbers both in soil and roots, in comparing with those of Vydate or induced by mixed compound was 97% and 70%; respectively in soil and roots. Rates of reproduction increase of the citrus nematode also reached 3% and 30% in both soil and roots; respectively. Vydate treatment resulted in a relatively lesser percentages. Growth of the concomitant fungus, Trichoderma sp. was increased specially in the last samples of October 2017, however those of fungi; Aspergillus flavus, Fusarium sp. And Rhizopus sp. was reduced, due to mixed compound treatment. Aspergillus niger and Penicillium sp. were not affected by the presence of the mixed compound. Vydate did not affect the co inhabitant fungi to a great extent.Â